Pendekatan Islam Dengan Nilai Penawaran: Keadilan, Kejujuran Dan Efisensi - Irmawanti, Irmawanti; Putri, Elen Sri Ega; Winario, Mohd (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to analyze the Islamic approach to supply values, especially those related to the principles of justice, honesty, and efficiency in economic activities. This study was conducted to identify how these values ​​are applied in the production, distribution, and trade processes, and their impact on market balance and social welfare. The study used a qualitative method with a literature analysis approach, involving a study of primary sources such as the Qur'an and Hadith, as well as contemporary Islamic economic literature. The results of the study indicate that the principle of justice in supply emphasizes the importance of fair distribution and avoidance of exploitation in trade. Honesty as a primary value in supply ensures that information provided by producers or sellers is transparent and free from fraud, thus creating trust between economic actors. Efficiency in the Islamic context is not only related to optimizing resources, but also ensuring that the production and distribution processes do not damage the environment or sacrifice the rights of others. The implementation of these values ​​has been proven to be able to create a more stable market and support the achievement of sharia goals (maqasid al-syariah), such as the welfare of the people and social justice.